Seroepidemiology of tetanus in Hangzhou from 2009 to 2018 - Yuyang Xu; Yan Liu; Jian Du; Wei Zheng; Shijun Liu; Xuechao Zhang; Xiaoping Zhang; Jun Wang; Xinren Che; Wenwen Gu; Wei Jiang (Human Vaccines & Immunotherapeutics, 2020)
Objective: The seroepidemiologic study aimed to delineate the immune status against tetanus in Hangzhou and its influential factors to provide evidence on strategies for tetanus prevention. Methods: We used a multi-stage stratified random sampling method to recruit participants from several Community Health Centers in Hangzhou during 2009–2018. Demographic data and vaccination histories of all subjects born during the period from 2004 to 2018 were collected from Hangzhou Immunization Information System (HZIIS), while the data of all subjects born before 2003 were acquired through case investigation. We used Enzyme Linked Immunosorbent Assay (ELISA) to detect Immunoglobulin G (IgG) antibodies against tetanus in serum samples and univariate and multivariate analysis to detect association between level of tetanus IgG and related factors. Results: A total of 3695 subjects were included, of which were 1904 males and 1791 females. About 59.84% of people had a clear immunization history of tetanus-toxoid-containing vaccines (TTCVs). The percentage of people whose tetanus IgG antibody titers were above the minimum protective level (0.1 IU/ml) was 76.02% (95% CI: 74.6–77.4%) and the geometric mean concentration (GMC) for tetanus IgG was 1.70 IU/ml. Antibody levels of people were higher in rural areas than in urban areas, in males than in females, in subjects who had inoculation vaccine history than those without inoculation of vaccine or with unknown history, and lower in groups aged >15 y compared to <15 y. Conclusions: The positive rate and GMC of tetanus IgG were significantly influenced by gender, age and immunization history of TTCVs. We should seek to achieve early and timely infant vaccination and maintain high coverage of the complete 3-dose primary series plus 3-dose booster series prior to adolescence. Besides basic immunization, we should stress the importance of using booster doses of tetanus vaccine in adolescents and adults; it is necessary to adopt corresponding immunization measures for women at childbearing age.